Methods for management of Tyrophagus putrescentiae (Schrank) (Sarcoptiformes: Acaridae) in dry-cured ham facilities - Abbar, Salehe (Kansas State University, 2016)
Dry-cured ham is protected from infestations of Tyrophagus putrescentiae (Schrank) (Sarcoptiformes: Acaridae) with the fumigant methyl bromide. Developing feasible alternatives to methyl bromide is necessary due to the phase out of methyl bromide. The effectiveness of food-safe compounds for preventing infestations of T. putrescentiae on dry-cured hams was evaluated by dipping ham pieces in solutions of various food additives. Propylene glycol (1, 2-propanediol), lard, ethoxyquin and butylated hydroxytoluene prevented or significantly reduced mite population growth. A combination of carrageenan + propylene glycol alginate + 40% propylene glycol was effective in reducing mite numbers on treated whole-aged hams compared with untreated hams. Dose/response tests with twelve registered residual insecticides were conducted to assess contact toxicity to T. putrescentiae. Three of these insecticides were evaluated for persistence over a 2-month period on different surfaces. Commercial formulations of deltamethrin plus chlorpyrifos-methyl, chlorfenapyr, and malathion showed promising results for contact toxicity against T. putriscentiae. Chlorfenapyr applied to metal, concrete, and wood resulted in 100% mortality of treated ham mites for up to 8 weeks. The effect of high and low temperatures on mortality of T. putrescentiae was studied in the laboratory. Groups of 10 eggs and groups of a mixture of 40 adults and nymphs were separately exposed to several high and low temperatures, ranging from +35 to 45°C and from −20 to +5°C, for several time periods. Eggs were found to be more tolerant to both high and low temperatures compared with adults and nymphs. Results showed that high temperatures from 40-45°C killed all T. putrescentiae eggs, adults, and nymphs within 4-1 d, while −10°C or lower killed all the same stages in less than 1 d. Combinations of the fumigant sulfuryl fluoride (SF) applied under high temperatures ranging from 25-40ºC, were studied to determine the highest temperature, shortest exposure time, and the lowest value of a concentration-by-time product (CTP) of SF against T. putrescentiae. Results showed that complete control of all life stages of T. putrescentiae was achieved at 40ºC with SF. More than one day of exposure was required to kill adults and nymphs and eggs at 40ºC at a CTP close to the EPA labeled rate of 1500 gh.m⁻³. Results indicated that adults and nymphs were more susceptible to SF compared to eggs. This study focused on investigating different control methods for T. putrescentiae in dry-cured ham facilities and most of examined techniques are preventive, although some of them can be applied as remedial methods after mite infestations are noticed.
Keywords: Tyrophagus putrescentiae (Schrank); Dry-cured ham; Integrated pest management; Methyl bromide alternatives